Determinants of Abortion in the Pandeglang District General Hospital - Harahap, Meilani; Eva Angraini; Nikmatul Khoiriyah Pulungan; Darma Afni Hasibuan; Rahmi Wahidah Siregar (PT Inovasi Pratama Internasional, 2022)
Abortion results from excessive bleeding due to cervical dilatation. Abortion is a threat or release of the results of conception before the fetus can live outside the womb of gestational age less than 20 weeks. In Indonesia the maternal mortality rate (MMR) in Indonesia is one of the highest in Southeast Asia, which is 228 per 100,000 live births. This research is to find out the determinants of the incidence of abortion in the Regional Hospital of Berkah Pandeglang . This type of research is quantitative analytic with a case control design with a ratio of 1: 1, using medical record data. The study population was all pregnant women in the Hospital of Berkah Pandeglang in 2019 namely 862, in the case of a population of 193 mothers who experienced abortion in 2019, the control population of mothers who did not experience abortion 669 in 2019. Sampling using a total sampling technique was obtained 193 and control samples using systematic random sampling that is 193. Analysis using univariate, bivariate with chi square test and multivariate with multiple logistic regression tests. The results of bivariate analysis obtained variables related to the incidence of abortion, namely age, parity, distance of pregnancy, education, history of abortion. Multivariate analysis results obtained a dominant variable, namely the distance of pregnancy with OR 5.114 after being controlled with parity, education, and history of abortion.